High-quality quadratic curve fitting for scanned data of styling design. (February 2016) - Tsuchie, Shoichi; Okamoto, Kunio
Abstract: We propose a new method for fitting a high-quality planar curve to styling design data by using a curvature continuous ( G 2 ) quadratic B-spline curve. In order to attain G 2 continuity of the B-spline curve, we use a non-uniform knot vector, which also enables the curve to be composed of fewer segments as compared to a uniform curve. In our method, control points and the knot vector of the B-spline curve are calculated separately; therefore, we can avoid solving a complicated nonlinear optimization problem. By conducting experiments, we demonstrate that high-quality curves can be generated from both artificial noisy data and real-world scanned data. Highlights: We propose a method for fitting a G 2 quadratic B-spline curve to planar styling design data. G 2 continuity is attained by using a non-uniform knot vector of the B-spline curve. High-quality curves have been obtained from noisy styling design data.